Packaging material for food freshness testing and method for its production
Patent Information
- Application Number
- CN202610798429.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-13
AI Technical Summary
但是,这种简单共混方式存在明显缺陷:一方面,荧光素钠作为小分子水溶物,在含水基质中易发生迁移和泄漏,存在向食品表面渗透的安全隐患;另一方面,游离的荧光素钠对光照敏感,在紫外激发下易发生光漂白,导致荧光信号衰减,影响指示可靠性
1.本申请提供的一种用于食品新鲜度检验的包装材料,当食品贮藏过程中,微生物代谢与蛋白质分解释放的挥发性盐基氮气体扩散至包装材料外层时,首先与氨基化介孔二氧化硅表面的氨基发生选择性亲和作用,被富集并导入介孔孔道内,孔道内限域的荧光素钠在新鲜状态下因局部微环境呈弱酸性/中性而以质子化形式存在,荧光较弱;随着胺类气体不断涌入,孔内pH升高至弱碱性,荧光素钠发生去质子化,其荧光显著增强,实现从“弱荧光→强荧光”的可视化转变,即可实现食品新鲜度的定量检验。
Smart Images

Figure CN122898083A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of food packaging materials technology, and in particular to a packaging material for testing the freshness of food and its preparation method. Background Technology
[0002] During storage and distribution, food components such as proteins and fats are easily decomposed due to microbial metabolism and endogenous enzyme activity, producing volatile basic nitrogenous substances such as ammonia, trimethylamine, and histamine. This leads to deterioration of food quality and even poses food safety risks. Traditional packaging only provides physical isolation and cannot reflect the real-time freshness of the food inside. Therefore, developing intelligent packaging materials that can monitor food freshness in situ, without damage, and in real time is of great significance for ensuring food safety, reducing waste, and improving the consumer experience.
[0003] Existing intelligent packaging technologies for food freshness can be mainly divided into two categories: colorimetric indication and fluorescence indication. In colorimetric indication, researchers typically disperse pH-sensitive dyes such as anthocyanins, alizarin red, or bromothymol blue directly in starch, polyvinyl alcohol, or cellulose matrices, using color changes to indicate alkaline gases produced during food spoilage. However, this approach relies on subjective color judgment by the naked eye, is easily affected by factors such as light source color temperature, film thickness, and individual observer differences, and can only provide a rough qualitative or semi-qualitative assessment, making quantitative detection difficult. Furthermore, natural pigments such as anthocyanins have poor photothermal stability and are prone to oxidative fading during long-term storage, leading to signal drift or even failure.
[0004] In fluorescence indication, sodium fluorescein and similar substances have attracted attention due to their high sensitivity and rapid response. Current technologies typically involve directly and physically blending sodium fluorescein into hydrogels or polymer films, utilizing the amine gases released during food spoilage to cause a local pH increase, thus causing the sodium fluorescein to transition from a weak to a strong fluorescent state. However, this simple blending method has significant drawbacks: firstly, as a small-molecule water-soluble compound, sodium fluorescein is prone to migration and leakage in aqueous matrices, posing a safety hazard of seeping into food surfaces; secondly, free sodium fluorescein is sensitive to light and is prone to photobleaching under ultraviolet excitation, leading to attenuation of the fluorescence signal and affecting the reliability of the indication.
[0005] Therefore, there is an urgent need to develop a packaging material for food freshness testing that has high sensitivity for quantitative detection and excellent stability. Summary of the Invention
[0006] In order to provide a smart packaging material with high sensitivity for quantitative detection, excellent stability, good mechanical properties and antibacterial preservation function, this application provides a packaging material for food freshness inspection and its preparation method.
[0007] This application provides a packaging material for testing the freshness of food, employing the following technical solution: A packaging material for testing the freshness of food, the raw materials of which include an outer casting solution, an inner casting solution, and an aqueous solution of calcium chloride; The raw materials of the outer casting solution include, by weight: 8-12 parts polyvinyl alcohol, 85-92 parts water, 1-3 parts sodium alginate, 0.5-1.5 parts sodium fluorescein-supported mesoporous silica, 0.01-0.05 parts fluorescent carbon quantum dots, 0.5-1.2 parts quaternized chitosan, and 1-2.5 parts glycerol; The raw materials of the inner layer casting solution include, by weight: 8-12 parts polyvinyl alcohol, 85-92 parts water, and 0.5-1.5 parts glycerol; The mass fraction of the calcium chloride aqueous solution is 1.5-3%.
[0008] Preferably, the fluorescent-loaded mesoporous silica is prepared from the following raw materials in parts by weight: 2-4 parts sodium fluorescein, 30-60 parts methanol, and 2-4 parts aminated mesoporous silica.
[0009] Preferably, the aminated mesoporous silica is prepared from the following raw materials in parts by weight: 2-3 parts mesoporous silica, 1.3-1.95 parts 3-aminopropyltriethoxysilane, and 40-60 parts toluene.
[0010] Preferably, the method for preparing the fluorescent-loaded mesoporous silica includes the following steps: Add 2-4 parts of sodium fluorescein to 30-60 parts of methanol and stir to dissolve. Then add 2-4 parts of aminated mesoporous silica and stir for 5-7 hours. Let stand, collect the solid, and after centrifugation, washing, and freeze drying, you will get fluorescent-loaded mesoporous silica.
[0011] Preferably, the method for preparing the aminated mesoporous silica includes the following steps: Add 2-3 parts of mesoporous silica and 1.3-1.95 parts of 3-aminopropyltriethoxysilane to 40-60 parts of toluene, reflux and stir at 85-95℃ for 24-30h. After the reaction is complete and cooled to room temperature, wash several times with toluene and then vacuum dry at 35-45℃ for 10-16h to obtain aminated mesoporous silica.
[0012] Preferably, the fluorescent carbon quantum dots are prepared from the following raw materials in parts by weight: 2-4 parts citric acid, 1-2 parts triethyltetramine, and 20-40 parts water.
[0013] Preferably, the method for preparing the fluorescent carbon quantum dots includes the following steps: Dissolve 2-4 parts of citric acid and 1-2 parts of triethyltetramine in 20-40 parts of water, mix with magnetic stirring for 15-25 minutes, transfer to a polytetrafluoroethylene reactor, and heat at 180-190℃ for 10-16 hours. After the reaction is complete, cool to room temperature, remove impurities by centrifugation and dialysis, and freeze-dry under vacuum to obtain fluorescent carbon quantum dots.
[0014] The method for preparing packaging material for food freshness testing provided in this application adopts the following technical solution: A method for preparing packaging material for food freshness testing includes the following steps: S1. Pour the outer layer casting solution into a PTFE mold and freeze until completely solidified; then immerse the mold in a calcium chloride aqueous solution for crosslinking for 2-4 hours; after removal, wash with PBS, wet the upper surface of the outer layer with a calcium chloride aqueous solution, and then cast the inner layer with the inner layer casting solution to form the inner layer, thus obtaining the composite hydrogel. S2. Freeze the composite hydrogel at -30 to (-20) °C for 12 to 14 hours, then thaw it at room temperature for 4 to 6 hours; repeat the freeze-thaw cycle 1 to 2 times. S3. After cutting the obtained composite hydrogel, place it in a sealed environment with RH>90% and equilibrate at room temperature for 48-60 hours until the water content reaches 80-85%, thus obtaining the packaging material for food freshness testing.
[0015] Preferably, the method for preparing the outer casting solution includes the following steps: Add 8-12 parts of polyvinyl alcohol to 85-92 parts of water and stir at 85-95℃ until dissolved; reduce the temperature to 60-70℃ and add 1-3 parts of sodium alginate, stirring for 1.5-3 hours; reduce the temperature to 35-45℃ and add 0.5-1.5 parts of fluorescent loaded mesoporous silica, 0.01-0.05 parts of fluorescent carbon quantum dots, 0.5-1.2 parts of quaternized chitosan, and 1-2.5 parts of glycerol in sequence, ultrasonically disperse for 40-60 minutes, stir in the dark for 30-50 minutes, and then degas under vacuum to obtain the outer casting solution.
[0016] Preferably, the method for preparing the inner layer casting solution includes the following steps: Add 8-12 parts of polyvinyl alcohol to 85-92 parts of water and stir at 85-95℃ until dissolved; cool to 35-45℃, add 0.5-1.5 parts of glycerol, stir for 30-50 minutes to remove bubbles, and the inner layer casting solution is obtained.
[0017] In summary, this application includes at least one of the following beneficial technical effects: 1. This application provides a packaging material for testing the freshness of food. When volatile basic nitrogen gas released by microbial metabolism and protein decomposition diffuses to the outer layer of the packaging material during food storage, it first undergoes selective affinity with the amino groups on the surface of aminated mesoporous silica, is enriched and introduced into the mesoporous channels. The fluorescein sodium confined in the channels exists in a protonated form in the fresh state due to the weakly acidic / neutral local microenvironment, resulting in weak fluorescence. As amine gases continuously enter, the pH inside the pores rises to a weakly alkaline state, and the fluorescein sodium undergoes deprotonation, significantly enhancing its fluorescence. This achieves a visual transformation from "weak fluorescence → strong fluorescence," thus enabling quantitative testing of food freshness.
[0018] 2. This application adopts an asymmetric gradient bilayer hydrogel configuration, which combines excellent mechanical properties with efficient mass transfer characteristics. The outer layer is a polyvinyl alcohol / sodium alginate composite layer loaded with fluorescent probes and functional additives. Through directional cryogenic casting, a longitudinally penetrating macroporous channel can be formed, which can rapidly capture and conduct volatile basic nitrogen released by food spoilage. The inner layer is a dense and transparent pure polyvinyl alcohol layer, which serves as a high-transmittance optical window to ensure that the fluorescence signal is transmitted to the outside of the packaging for observation without attenuation. Attached Figure Description
[0019] Figure 1 This is a SEM image (50 μm) of the packaging material prepared in Example 1 of this application.
[0020] Figure 2 This is a SEM image (50 μm) of the packaging material prepared in Example 1 of this application.
[0021] Figure 3 The result is the change in fluorescence intensity of the packaging material prepared in Example 1 of this application as fresh milk deteriorates. Detailed Implementation
[0022] The present application will be further described in detail below with reference to the embodiments.
[0023] The chemical reagents used in the preparation examples, embodiments, and comparative examples provided in this invention are all commercially available products, and their brands and manufacturers are as follows: Polyvinyl alcohol, Shanghai Aladdin Biochemical Technology Co., Ltd., Product No.: P105124; Sodium alginate, Wuhan Jiyesheng Chemical Co., Ltd.; Quaternized chitosan, Guangdong Wengjiang Chemical Reagent Co., Ltd.; Sodium fluorescein, Shanghai Aladdin Biochemical Technology Co., Ltd., Product No.: F809553; Glycerin, Taishan Changshun Glycerin Products Co., Ltd.
[0024] Preparation Example 1: Preparation of Sodium Fluorescein Supported Mesoporous Silica Preparation Example 1.1 S1. Add 2g of mesoporous silica and 1.3g of 3-aminopropyltriethoxysilane to 40g of toluene, reflux and stir at 85℃ for 24h. After the reaction is complete and cooled to room temperature, wash with toluene 3 times and dry under vacuum at 35℃ for 10h to obtain aminated mesoporous silica. S2. Add 2g of sodium fluorescein to 30g of methanol and stir to dissolve. Then add 2g of aminated mesoporous silica prepared by S1 and stir for 5h. Let stand, collect the solid, wash it three times with ethanol by centrifugation, and freeze dry to obtain sodium fluorescein-supported mesoporous silica.
[0025] Preparation Example 1.2 S1. Add 2.5g of mesoporous silica and 1.6g of 3-aminopropyltriethoxysilane to 50g of toluene, reflux and stir at 90℃ for 27h. After the reaction is complete and cooled to room temperature, wash with toluene 4 times and dry under vacuum at 40℃ for 13h to obtain aminated mesoporous silica. S2. Add 3g of sodium fluorescein to 45g of methanol and stir to dissolve. Then add 3g of aminated mesoporous silica prepared by S1 and stir for 6 hours. Let stand, collect the solid, wash it 4 times with ethanol by centrifugation, and freeze dry to obtain sodium fluorescein-supported mesoporous silica.
[0026] Preparation Example 1.3 S1. Add 3g of mesoporous silica and 1.95g of 3-aminopropyltriethoxysilane to 60g of toluene, reflux and stir at 95℃ for 30h, after the reaction is complete and cooled to room temperature, wash with toluene 5 times, and then vacuum dry at 45℃ for 16h to obtain aminated mesoporous silica. S2. Add 4g of sodium fluorescein to 60g of methanol and stir to dissolve. Then add 4g of aminated mesoporous silica prepared by S1 and stir for 7h. Let stand, collect the solid, wash it 5 times with ethanol by centrifugation, and freeze dry to obtain sodium fluorescein-supported mesoporous silica.
[0027] Preparation Example 2: Preparation of Fluorescent Carbon Quantum Dots Preparation Example 2.1 2g of citric acid and 1g of triethyltetramine were dissolved in 20g of deionized water and mixed with magnetic stirring for 15min. The mixture was then transferred to a polytetrafluoroethylene reactor and heated at 180℃ for 10h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, dialyzed with a dialysis bag (1000Da) for 48h, and then freeze-dried under vacuum to obtain fluorescent carbon quantum dots.
[0028] Preparation Example 2.2 3g of citric acid and 1.5g of triethyltetramine were dissolved in 30g of deionized water and mixed with magnetic stirring for 20min. The mixture was then transferred to a polytetrafluoroethylene reactor and heated at 185℃ for 13h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, dialyzed with a dialysis bag (1000Da) for 54h, and then freeze-dried under vacuum to obtain fluorescent carbon quantum dots.
[0029] Preparation Example 2.3 4g of citric acid and 2g of triethyltetramine were dissolved in 40g of deionized water and mixed with magnetic stirring for 25min. The mixture was then transferred to a polytetrafluoroethylene reactor and heated at 190℃ for 16h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, dialyzed with a dialysis bag (1000Da) for 60h, and then freeze-dried under vacuum to obtain fluorescent carbon quantum dots.
[0030] Example 1
[0031] S1. Add 8g of polyvinyl alcohol to 85g of water and stir at 85°C until dissolved; reduce the temperature to 60°C, add 1g of sodium alginate, and stir for 1.5h; reduce the temperature to 35°C, and add 0.5g of sodium fluorescein-supported mesoporous silica prepared in Preparation Example 1.1, 0.01g of fluorescent carbon quantum dots prepared in Preparation Example 2.1, 0.5g of quaternized chitosan, and 1g of glycerol in sequence. Disperse by ultrasonication for 40min, stir in the dark for 30min, and then degas under vacuum for 15min to obtain the outer casting solution. Add 8g of polyvinyl alcohol to 85g of water and stir at 85℃ until dissolved; reduce the temperature to 35℃, add 0.5g of glycerol, stir for 30min, and vacuum degas for 15min to obtain the inner layer casting solution. S2. Pour the outer layer casting solution into a PTFE mold (with a -40℃ copper plate attached to the bottom and the top exposed to 25℃ air), freeze until completely solidified; then immerse the mold in a 1.5% calcium chloride aqueous solution for crosslinking for 2 hours; after removal, wash with PBS, wet the upper surface of the outer layer with a 1.5% calcium chloride aqueous solution, and then cast the inner layer with the inner layer casting solution to form the inner layer, thus obtaining the composite hydrogel; S3. Freeze the composite hydrogel at -30℃ for 12 hours, then thaw it at room temperature for 4 hours; repeat the freeze-thaw cycle once. S4. After cutting the obtained composite hydrogel into 20mm×30mm samples, place them in a sealed environment with RH>90% and equilibrate at room temperature for 48 hours until the water content reaches 80-85%, thus obtaining packaging materials for food freshness testing.
[0032] Example 2
[0033] S1. Add 10g of polyvinyl alcohol to 89g of water and stir at 85°C until dissolved; reduce the temperature to 60°C, add 2g of sodium alginate, and stir for 1.5h; reduce the temperature to 35°C, and add 1g of sodium fluorescein-supported mesoporous silica prepared in Preparation Example 1.1, 0.03g of fluorescent carbon quantum dots prepared in Preparation Example 2.1, 0.9g of quaternized chitosan, and 1.7g of glycerol in sequence, sonicate for 40min, stir in the dark for 30min, and then degas under vacuum for 15min to obtain the outer casting solution; Add 10g of polyvinyl alcohol to 89g of water and stir at 85℃ until dissolved; reduce the temperature to 35℃, add 1g of glycerol, stir for 30min, and vacuum degas for 15min to obtain the inner layer casting solution. S2. Pour the outer layer casting solution into a PTFE mold (with a -40℃ copper plate attached to the bottom and the top exposed to 25℃ air), freeze until completely solidified; then immerse the mold in a 1.5% calcium chloride aqueous solution for crosslinking for 2 hours; after removal, wash with PBS, wet the upper surface of the outer layer with a 1.5% calcium chloride aqueous solution, and then cast the inner layer with the inner layer casting solution to form the inner layer, thus obtaining the composite hydrogel; S3. Freeze the composite hydrogel at -30℃ for 12 hours, then thaw it at room temperature for 4 hours; repeat the freeze-thaw cycle once. S4. After cutting the obtained composite hydrogel into 20mm×30mm samples, place them in a sealed environment with RH>90% and equilibrate at room temperature for 48 hours until the water content reaches 80-85%, thus obtaining packaging materials for food freshness testing.
[0034] Example 3
[0035] S1. Add 12g of polyvinyl alcohol to 92g of water and stir at 85°C until dissolved; reduce the temperature to 60°C, add 3g of sodium alginate, and stir for 1.5h; reduce the temperature to 35°C, and add 1.5g of sodium fluorescein-supported mesoporous silica prepared in Preparation Example 1.1, 0.05g of fluorescent carbon quantum dots prepared in Preparation Example 2.1, 1.2g of quaternized chitosan, and 2.5g of glycerol in sequence, sonicate for 40min, stir in the dark for 30min, and then degas under vacuum for 15min to obtain the outer casting solution; Add 12g of polyvinyl alcohol to 92g of water and stir at 85℃ until dissolved; reduce the temperature to 35℃, add 1.5g of glycerol, stir for 30min, and vacuum degas for 15min to obtain the inner layer casting solution. S2. Pour the outer layer casting solution into a PTFE mold (with a -40℃ copper plate attached to the bottom and the top exposed to 25℃ air), freeze until completely solidified; then immerse the mold in a 1.5% calcium chloride aqueous solution for crosslinking for 2 hours; after removal, wash with PBS, wet the upper surface of the outer layer with a 1.5% calcium chloride aqueous solution, and then cast the inner layer with the inner layer casting solution to form the inner layer, thus obtaining the composite hydrogel; S3. Freeze the composite hydrogel at -30℃ for 12 hours, then thaw it at room temperature for 4 hours; repeat the freeze-thaw cycle once. S4. After cutting the obtained composite hydrogel into 20mm×30mm samples, place them in a sealed environment with RH>90% and equilibrate at room temperature for 48 hours until the water content reaches 80-85%, thus obtaining packaging materials for food freshness testing.
[0036] Example 4
[0037] S1. Add 8g of polyvinyl alcohol to 85g of water and stir at 90°C until dissolved; reduce the temperature to 65°C, add 1g of sodium alginate, and stir for 1.5h; reduce the temperature to 40°C, and add 0.5g of sodium fluorescein-supported mesoporous silica prepared in Preparation Example 1.2, 0.01g of fluorescent carbon quantum dots prepared in Preparation Example 2.2, 0.5g of quaternized chitosan, and 1g of glycerol in sequence. Disperse by ultrasonication for 50min, stir in the dark for 40min, and then degas under vacuum for 20min to obtain the outer casting solution. Add 8g of polyvinyl alcohol to 85g of water and stir at 90℃ until dissolved; reduce the temperature to 40℃, add 0.5g of glycerol, stir for 40min, and degas under vacuum for 20min to obtain the inner layer casting solution. S2. Pour the outer layer casting solution into a PTFE mold (with a -40℃ copper plate attached to the bottom and the top exposed to 25℃ air), freeze until completely solidified; then immerse the mold in a 2% calcium chloride aqueous solution for crosslinking for 3 hours; after removal, clean with PBS, wet the upper surface of the outer layer with a 2% calcium chloride aqueous solution, and then cast the inner layer with the inner layer casting solution to form the inner layer, thus obtaining the composite hydrogel; S3. Freeze the composite hydrogel at -25℃ for 13 hours, then thaw it at room temperature for 5 hours; repeat the freeze-thaw cycle once. S4. After cutting the obtained composite hydrogel into 20mm×30mm samples, place them in a closed environment with RH>90% and equilibrate at room temperature for 54 hours until the water content reaches 80-85%, thus obtaining the packaging material for food freshness testing.
[0038] Example 5
[0039] S1. Add 8g of polyvinyl alcohol to 85g of water and stir at 95°C until dissolved; reduce the temperature to 70°C, add 1g of sodium alginate, and stir for 1.5h; reduce the temperature to 45°C, and add 0.5g of sodium fluorescein-supported mesoporous silica prepared in Preparation Example 1.3, 0.01g of fluorescent carbon quantum dots prepared in Preparation Example 2.3, 0.5g of quaternized chitosan, and 1g of glycerol in sequence. Disperse by ultrasonication for 60min, stir in the dark for 50min, and then degas under vacuum for 25min to obtain the outer casting solution. Add 8g of polyvinyl alcohol to 85g of water and stir at 95℃ until dissolved; reduce the temperature to 45℃, add 0.5g of glycerol, stir for 50min, and vacuum degas for 25min to obtain the inner layer casting solution. S2. Pour the outer layer casting solution into a PTFE mold (with a -40℃ copper plate attached to the bottom and the top exposed to 25℃ air), freeze until completely solidified; then immerse the mold in a 3% calcium chloride aqueous solution for crosslinking for 4 hours; after removal, clean with PBS, wet the upper surface of the outer layer with a 3% calcium chloride aqueous solution, and then cast the inner layer with the inner layer casting solution to form the inner layer, thus obtaining the composite hydrogel; S3. Freeze the composite hydrogel at -20℃ for 14 hours, then thaw it at room temperature for 6 hours; repeat the freeze-thaw cycle twice. S4. After cutting the obtained composite hydrogel into 20mm×30mm samples, place them in a closed environment with RH>90% and equilibrate at room temperature for 60h until the water content reaches 80-85%, thus obtaining the packaging material for food freshness testing.
[0040] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that an equal amount of sodium fluorescein is used instead of the fluorescent-loaded mesoporous silica prepared in Preparation Example 1.1.
[0041] Performance testing I. The tensile strength and elongation at break of the packaging materials obtained in Examples 1-5 and Comparative Example 1 were tested in accordance with GB / T 1040.1-2025 "Determination of tensile properties of plastics - Part 1: General". The results are shown in Table 1.
[0042] The specific test results are as follows: Table 1 Performance Test Results Example 1 8.1 243 Example 2 8.8 259 Example 3 8.5 230 Example 4 8.6 251 Example 5 9.0 247 Comparative Example 1 4.7 208 As can be seen from the test results in Table 1, the packaging material provided in this application for food freshness testing also has high tensile strength and elongation at break, indicating that it has good mechanical properties.
[0043] II. The surface features of the packaging material obtained in Example 1 were examined using a scanning electron microscope, and the results are as follows: Figure 1 , Figure 2 As shown.
[0044] III. With the outer layer (macroporous layer) of the packaging material obtained in Example 1 facing the food, it was attached to the PTFE microporous membrane using food-grade pressure-sensitive adhesive. The PTFE membrane was then heat-sealed onto the inside of the PP / PE outer packaging film. After containing 500ml of fresh milk, the changes in the fluorescence intensity of the packaging material as the milk deteriorated were observed. The results are as follows: Figure 3 As shown.
[0045] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A packaging material for testing the freshness of food, characterized in that: The raw materials include outer layer casting solution, inner layer casting solution, and calcium chloride aqueous solution; The raw materials of the outer casting solution include, by weight: 8-12 parts polyvinyl alcohol, 85-92 parts water, 1-3 parts sodium alginate, 0.5-1.5 parts sodium fluorescein-supported mesoporous silica, 0.01-0.05 parts fluorescent carbon quantum dots, 0.5-1.2 parts quaternized chitosan, and 1-2.5 parts glycerol; The raw materials of the inner layer casting solution include, by weight: 8-12 parts polyvinyl alcohol, 85-92 parts water, and 0.5-1.5 parts glycerol; The mass fraction of the calcium chloride aqueous solution is 1.5-3%.
2. The packaging material for food freshness testing according to claim 1, characterized in that: The sodium fluorescein-supported mesoporous silica is prepared from the following raw materials in parts by weight: 2-4 parts sodium fluorescein, 30-60 parts methanol, and 2-4 parts aminated mesoporous silica.
3. The packaging material for food freshness testing according to claim 2, characterized in that: The aminated mesoporous silica is prepared from the following raw materials in parts by weight: 2-3 parts mesoporous silica, 1.3-1.95 parts 3-aminopropyltriethoxysilane, and 40-60 parts toluene.
4. The packaging material for food freshness testing according to claim 2, characterized in that: The method for preparing sodium fluorescein-supported mesoporous silica includes the following steps: Add 2-4 parts of sodium fluorescein to 30-60 parts of methanol and stir to dissolve. Then add 2-4 parts of aminated mesoporous silica and stir for 5-7 hours. Let stand, collect the solid, and after centrifugation, washing, and freeze drying, you will get sodium fluorescein-supported mesoporous silica.
5. The packaging material for food freshness testing according to claim 3, characterized in that: The method for preparing the aminated mesoporous silica includes the following steps: Add 2-3 parts of mesoporous silica and 1.3-1.95 parts of 3-aminopropyltriethoxysilane to 40-60 parts of toluene, reflux and stir at 85-95℃ for 24-30h. After the reaction is complete and cooled to room temperature, wash several times with toluene and then vacuum dry at 35-45℃ for 10-16h to obtain aminated mesoporous silica.
6. The packaging material for food freshness testing according to claim 1, characterized in that: The fluorescent carbon quantum dots are prepared from the following raw materials in parts by weight: 2-4 parts citric acid, 1-2 parts triethyltetramine, and 20-40 parts water.
7. A packaging material for food freshness testing according to claim 6, characterized in that: The method for preparing the fluorescent carbon quantum dots includes the following steps: Dissolve 2-4 parts of citric acid and 1-2 parts of triethyltetramine in 20-40 parts of water, mix with magnetic stirring for 15-25 minutes, transfer to a polytetrafluoroethylene reactor, and heat at 180-190℃ for 10-16 hours. After the reaction is complete, cool to room temperature, remove impurities by centrifugation and dialysis, and freeze-dry under vacuum to obtain fluorescent carbon quantum dots.
8. A method for preparing a packaging material for food freshness testing according to any one of claims 1-7, characterized in that: Includes the following steps: S1. Pour the outer layer casting solution into a PTFE mold and freeze until completely solidified; then immerse the mold in a calcium chloride aqueous solution for crosslinking for 2-4 hours; after removal, wash with PBS, wet the upper surface of the outer layer with a calcium chloride aqueous solution, and then cast the inner layer with the inner layer casting solution to form the inner layer, thus obtaining the composite hydrogel. S2. Freeze the composite hydrogel at -30 to (-20) °C for 12 to 14 hours, then thaw it at room temperature for 4 to 6 hours; repeat the freeze-thaw cycle 1 to 2 times. S3. After cutting the obtained composite hydrogel, place it in a sealed environment with RH>90% and equilibrate at room temperature for 48-60 hours until the water content reaches 80-85%, thus obtaining the packaging material for food freshness testing.
9. A method for preparing packaging material for food freshness testing according to claim 8, characterized in that: The method for preparing the outer casting solution includes the following steps: Add 8-12 parts of polyvinyl alcohol to 85-92 parts of water and stir at 85-95℃ until dissolved; reduce the temperature to 60-70℃ and add 1-3 parts of sodium alginate, stirring for 1.5-3 hours; reduce the temperature to 35-45℃ and add 0.5-1.5 parts of sodium fluorescein-supported mesoporous silica, 0.01-0.05 parts of fluorescent carbon quantum dots, 0.5-1.2 parts of quaternized chitosan, and 1-2.5 parts of glycerol in sequence, ultrasonically disperse for 40-60 minutes, stir in the dark for 30-50 minutes, and then degas under vacuum to obtain the outer casting solution.
10. A method for preparing packaging material for food freshness testing according to claim 8, characterized in that: The method for preparing the inner layer casting solution includes the following steps: Add 8-12 parts of polyvinyl alcohol to 85-92 parts of water and stir at 85-95℃ until dissolved; cool to 35-45℃, add 0.5-1.5 parts of glycerol, stir for 30-50 minutes to remove bubbles, and the inner layer casting solution is obtained.